2019
DOI: 10.1016/j.parkreldis.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Which disease features run in essential tremor families? A systematic review

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Moreover, the current study found that ET plus patients were generally older and had a longer disease duration than ET patients, suggesting that ET plus may represent a relatively late feature in long-standing ET patients. It is well known that alcohol responsiveness is a common feature of ET [ 40 , 41 ]. Most patients with a history of drinking experienced an improvement in their tremors with alcohol consumption, and there was no significant difference between ET plus and ET patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current study found that ET plus patients were generally older and had a longer disease duration than ET patients, suggesting that ET plus may represent a relatively late feature in long-standing ET patients. It is well known that alcohol responsiveness is a common feature of ET [ 40 , 41 ]. Most patients with a history of drinking experienced an improvement in their tremors with alcohol consumption, and there was no significant difference between ET plus and ET patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary history including consumption of alcohol 14 or environmental history that contributes to essential tremor pathogenesis could provide clues for etiologic origins. Some interest has been shown in assessing the relationship between high amounts of meat in the diet and linkage with essential tremor because harmane, which has tremorgenic properties, is abundantly present in meat 15 .…”
Section: Diet and Social Historymentioning
confidence: 99%
“…Ascertainment of family history is critical because essential tremor has shown high rates (30% to 70%) of heritability 14,21 . The family history is often consistent with a Mendelian pattern of inheritance 14 .…”
Section: Family Historymentioning
confidence: 99%
See 1 more Smart Citation
“…A historical cohort of 162 patients with PD and their relatives found a higher risk of ET in family members of PD probands with age at onset under 67 (HR 2.24, p = 0.006) [107]. Certain characteristics, such as age at onset, disease progression, alcohol responsiveness, parkinsonism and dystonia, have been found to aggregate in some families [114].…”
Section: Essential Tremormentioning
confidence: 99%